ChemInform Abstract: Concise Total Syntheses of Pyrido[4, 3‐b]carbazole Alkaloids Using Copper‐Mediated 6π‐Electrocyclization. Issue 36 (August 2016) - Itoh, Tomoki; Abe, Takumi; Choshi, Tominari; Nishiyama, Takashi; Yanada, Reiko; Ishikura, Minoru
Abstract: Cu‐catalyzed 6π‐electrocyclization of triene‐substrates of type (I) provides a facile access to pyrido[4, 3‐b]carbazoles, which represent advanced intermediates for the construction of various ellipticine and olivacine alkaloids.